Efficacy of Neem Oil on the Biology and Food Consumption of Epilachna Beetle, Epilachna dodecastigma (Wied.) - Anam, M; Ahmad, Masum; Haque, MA (Journal of Agriculture & Rural Development, 2008)
The efficacy of neem oil on the mortality, growth and feeding responses of epilachna beetle showed that all the larval instars were susceptible to this oil. The LC50 values were higher at 3rd instar and it was lowest on 1st instar. The LT50 values of oil increases proportionately with increasing larval age and with decreasing oil concentration. Neem oil significantly prolonged larval and pupal periods and some of the treated larvae never reached to the pupae. Pupal recovery and adult emergence were greatly reduced in treated larvae. In addition, neem oil also reduced the food consumption of this beetle by acting as feeding deterrent. Key words: Neem oil, mortality, growth, feeding response, Epilachna dodecastigma.